Long-term settlement prediction at closed dumping area using hyperbolic function model - Shariffuddin A.S.; Pauzi N.I.M.; Hosni A.A. (E-Journal of Geotechnical Engineering, 2023)
Forecasting; Land fill; Settlement of structures; Soils; Empirical model; Final settlement; Geotechnical properties; Initial rate; Long term settlement; Settlement models; Settlement rate; Waste soils; Hyperbolic functions; empirical analysis; geotechnical engineering; geotechnical property; ground settlement; landfill; numerical model; prediction; Malaysia